PERANAN EXECUTIVE LOUNGE ATTENDENT TERHADAP TINGKAT KEPUASAN TAMU DI SHERATON BANDUNG HOTEL & TOWERS - Toni Andriyono; Seffa Aryanti (LPPM Politeknik Pajajaran ICB Bandung, 2025)
Service in the Executive Lounge is one of the key factors in creating a memorable guest experience in five-star hotels. This study aims to analyze the role of Executive Lounge Attendants in relation to guest satisfaction at Sheraton Bandung Hotel and Towers. The research method used is a descriptive qualitative approach with data collection techniques including observation, in-depth interviews, and documentation study. The findings indicate that the roles of Executive Lounge Attendants include welcoming guests, providing food and beverage service, delivering information, and handling special guest needs. Friendly, prompt, and professional service quality significantly contributes to guest satisfaction. In conclusion, Executive Lounge Attendants play a strategic role in creating comfort, loyalty, and a positive image of the hotel. The recommendations proposed are continuous training, service standardization, and regular evaluation of guest satisfaction. Keywords: Executive Lounge, Attendant, Service, Guest Satisfaction, Sheraton Bandung Hotel